Central nervous system regulation of intestinal lipid and lipoprotein metabolism. Issue 1 (February 2016) - Farr, Sarah; Taher, Jennifer; Adeli, Khosrow
Abstract : Purpose of review: In response to nutrient availability, the small intestine and brain closely communicate to modulate energy homeostasis and metabolism. The gut-brain axis involves complex nutrient sensing mechanisms and an integration of neuronal and hormonal signaling. This review summarizes recent evidence implicating the gut-brain axis in regulating lipoprotein metabolism, with potential implications for the dyslipidemia of insulin resistant states. Recent findings: The intestine and brain possess distinct mechanisms for sensing lipid availability, which triggers subsequent regulation of feeding, glucose homeostasis, and adipose tissue metabolism. More recently, central receptors, neuropeptides, and gut hormones that communicate with the brain have been shown to modulate hepatic and intestinal lipoprotein metabolism via parasympathetic and sympathetic signaling. Gut-derived glucagon-like peptides appear to be particularly important in modulating the intestinal secretion of chylomicron particles via a novel brain-gut axis. Dysregulation of these pathways may contribute to postprandial diabetic dyslipidemia. Summary: Emerging evidence implicates the central and enteric nervous systems in controlling many aspects of lipid and lipoprotein metabolism. Bidirectional communication between the gut and brain involving neuronal pathways and gut peptides is critical for regulating feeding and metabolism, and forms a neuroendocrine circuit to modulate dietary fat absorption and intestinal production of atherogenic chylomicron particles.